ANALYSIS OF READING EXERCISE QUESTIONS IN AN ENGLISH TEXTBOOK FOR YEAR X SENIOR HIGH SCHOOL STUDENTS BASED ON BLOOM’S - MAHMUD LAYAN HUTASUHUT; RATNA SARI SILALAHI (State University of Medan, 2022)
This research identifies the distribution of reading exercise questions based on the cognitive domains in the Revised Bloom's Taxonomy. It also attempts to change the reading exercise questions from the Lower-order Thinking Skills (LOTS) items into Higher-order Thinking Skills (HOTS) items. Content analysis was used as the research methodology. The subject of the study was the English textbook ‘Bahasa Inggris SMA/MA/SMK/MAK’ for year X high school students published by the Ministry of Education and Culture. Documentation was employed to collect data. The data were analyzed by using an interactive mood technique. Results of the study revealed that the lower-order thinking skills were distributed within 183 items, while that of the higher-order thinking skills were within 63 items. Specifically, the lower order thinking skills items were distributed as follows: Remembering skill with 100 questions, or 41%, understanding skill with 31 items, or 13%, and applying skill with 52 reading questions, or 21%. Meanwhile, the higher order thinking skills comprised analyzing skill with 38 questions or 15%, evaluating skill with 13 questions or 15%, and creating skills with 12 questions, or 5%. To sum up, the data showed the distribution of the higher order thinking skill (25%) was significantly lower than that of lower order thinking skill (75%).